Analysis of the probability implementation of threats protection of information in industrial control systems - Гончар, Сергій Феодосійович (Ukrainian Information Security Research Journal, 2014)
For the purpose of the decision of the tasks connected to support of information security of industrial control systems the analysis of threats of information security and the detailed description of sources of deliberate threats is carried out. The analysis of vulnerabilities information security of the industrial control systems, classification and the reasons of their origin is made. Recommendations about elimination or leveling of these vulnerabilities are made. Expression for determination of probability of implementation of threats of the information is resulted. Correlations between threats, vulnerabilities and risk for the industrial control systems are researched. Lifecycle of probability of implementation of threats of information security of the industrial control systems is resulted and the initial data necessary for the given analysis is formulated.